Scattering reduction by structured light illumination in line-scanning temporal focusing microscopy - Xue, Yi (Biomed Opt Express, 2018)
Line-scanning temporal focusing microscopy (LineTFM) is capable of imaging biological samples more than 10 times faster than two-photon laser point-scanning microscopy (TPLSM), while achieving nearly the same lateral and axial spatial resolution. However, the image contrast taken by LineTFM is lower than that by TPLSM because LineTFM is severely influenced by biological tissue scattering. To reject the scattered photons, we implemented LineTFM using both structured illumination and uniform illumination combined with the HiLo post-processing algorithm, called HiLL microscopy (HiLo-Line-scanning temporal focusing microscopy). HiLL microscopy significantly reduces tissue scattering and improves image contrast. We demonstrate HiLL microscopy with in vivo brain imaging. This approach could potentially find applications in monitoring fast dynamic events and in mapping high resolution structures over a large volume.